The Relationship between Teacher Support and Students' Academic Emotions: A Meta-Analysis - Lei, Hao; Cui, Yunhuo; Chiu, Ming Ming (Frontiers in Psychology, 2018)
This meta-analysis examines the association between teacher support and students’ academic emotions (both positive academic emotions [PAEs] and negative academic emotions [NAEs]) and explores how student characteristics moderate these relationships. We identified 65 primary studies with 58,368 students. The results provided strong evidence linking teacher support and students’ academic emotions. Furthermore, students’ culture, age, and gender moderated these links. The correlation between teacher support and PAEs was stronger for Western European and American students than for East Asian students, while the correlation between teacher support and NAEs was stronger for East Asian students than for Western European and American students. Also, the correlation between teacher support and PAEs was strong among university students and weaker among middle school students, compared to other students. The correlation between teacher support and NAEs was stronger for middle school students and for female students, compared to other students.